O aggiornamento do pentecostalismo: as assembleias de Deus no Brasil e na cidade de Imperatriz - MA (1980-2010) - Costa, Moab César Carvalho (Universidade do Vale do Rio dos Sinos, 2017)
The present work intends to study the Brazilian Pentecostal movement through one of its major institutions, the Igrejas Evangélicas Assembleias de Deus (Assemblies of God Evangelical Churches) - AGs. With an approach anchored in the interdisciplinary dialogues with the Social Sciences, recommended by the New Cultural History, we analyze the changes in the identity of the classical assembly, in the process of accommodation to the society of consumers, a fact that we call the aggiornamento of the assemblian Pentecostalism. Founded by the Swedish Missionaries Daniel Berg and Gunnar Vingren in 1911, the AGs started the Pentecostal movement in partnership with the Christian Congregation of Brazil (CCB). One hundred years after its founding, they are found in most of the Brazilian municipalities and, according to the IBGE (Brazilian Institute of Geography and Statistics) census, they already have over 12 million followers. Although the temporality of the survey is limited to the period from 1980 to 2010, a historical analysis was carried out, dating back to the 19th century, in search of its original influences. One of the axes that guided the research was the idea that religious institutions representing Christianity always reflected the society of its time. Based on this premise, it was possible to perceive that the AGs conformed to the characteristics of Brazilian society in each phase of its history: they were ascetic and sectarian when the society was rural and very poor; propagated an exacerbated patriarchal authoritarianism when women could not vote and did not have their rights guaranteed by law; they were not involved in political parties and did not manifest themselves publicly repudiating social injustices; his discourse and theological standard prevailed for a life of behavioral austerity and resigned waiting for the apocalyptic return of Jesus Christ. Faced with a socioeconomic and cultural reality in constant transformation, under the influence of consumer capitalism and, in order to face competition in the religious field, especially after the arrival of neo-Pentecostal churches, the institution implemented significant changes, which accelerated the process of transformation of ethos. Categories such as consumption, identity, relativism, secularization, pluralism, religious freedom, representations, strategies and tactics, present time, among others, supported the construction of the research object. The studies are focused on the General Convention of Assemblies of God in Brazil - CGADB and the AGs of the city of Imperatriz, Brazil.
Keywords: Aggiornamento do pentecostalismo; Consumo; Identidade; Assembleias de Deus; Imperatriz-MA; Brasil; Aggiornamento of pentecostalism; Consumption; Identity; Assemblies of god; Imperatriz; Brazil; ACCNPQ::Ciências Humanas::História